(3GdQSGdI GdhVhFjI aj GdQSGFd GdTQYjI GdeUWahjIs - (3edG NSQh, eMeO Hf aQGehR Hf Ydj, J (B885 (3g`s ((3EHQGgje Hf YeQ TGg aQPObs)
(3ChdgG (B:s
(3HYO GdHSedI ; CMeOg hgh HGdMeO LOjQ CeG HYO aEfj SeYJ Cf YdeGA GdHdOI HeOjfI bSWfWjfjI Cf GdcdeGJ aj GdYhGQV HOhf GdcdeGJ aLeYJ eNJUQG TGedG dgeG hSejJg HGdQSGdI GdhVhFjIs
(3BNQgG (B:s
(3hGdJhVF aj GdMhV CaVd ef GdJhVF GdLGQj QZeG ddeYJRdI HfGA Ydi eSCdI GdLRA GdPj dG jJLRCs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe (B6 / 328s
(3eYLe GdeDdajf (B3 / 584s
(3TPQGJ GdPgH (B7 / 342s
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdbWQjIs
Keywords: (3Gdabg GdMfHdjs